Kajian Psikologi Humanistik Tokoh Utama Dalam Novel Merindu Cahaya de Amstel Karya Arumi E. - Wiji Utari; Enny Rahayu (Medan Resource Center, 2023)
This study aims to describe the humanistic psychological needs of the characters Khadija and Nico in the novel Merindu Cahaya de Amstel by Arumi E. with a literary psychology approach. The source of research data is the novel Merindu Cahaya de Amstel by Arumi E. totaling 271 pages published by PT Gramedia Pustaka Utama, Jakarta, the first printing in 2015. The data for this research is the needs of the characters Khadija and Nico in the novel Merindu Cahaya de Amstel by Arumi E. The method used used in this research is descriptive method by collecting data, describing data, and analyzing data. The instrument used in this study is a documentation guide. The data analysis technique used is to read the novel repeatedly, to appreciate, to understand, to collect data, to underline, to describe and to conclude the research results. The results of this study are able to answer research questions that contain humanistic psychological needs including physiological needs, needs for security, needs for belonging and love, needs for self-esteem, and needs for self-actualization in Khadija and Nico characters.